1999
DOI: 10.1016/s0925-4773(98)00205-6
|View full text |Cite
|
Sign up to set email alerts
|

Expression of growth/differentiation factor 11, a new member of the BMP/TGFβ superfamily during mouse embryogenesis

Abstract: We have cloned and characterized a new member of the bone morphogenetic protein/transforming growth factor beta (BMP/TGFbeta) superfamily, growth differentiation factor 11 (Gdf11), from rat incisor pulp RNA by reverse transcription-polymerase chain reaction using degenerate primers. The mature carboxyl-terminal domain encoded by Gdf11 is most closely related to Gdf8, being 90% identical to the mouse gene. Northern blot analysis revealed Gdf11 is expressed in adult dental pulp and brain. In situ hybridization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
200
1
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(214 citation statements)
references
References 9 publications
11
200
1
2
Order By: Relevance
“…Firstly, myostatin (GDF8) is a close structural homologue of GDF11, with 90% amino acid sequence identity shared in their mature activeforms. 40 Thus, our assay for mouse and human serum GDF11 does not distinguish circulating GDF11 and GDF8. As a result, we did not accurately determine the changes of GDF11 in mice and in human.…”
Section: Discussionmentioning
confidence: 84%
“…Firstly, myostatin (GDF8) is a close structural homologue of GDF11, with 90% amino acid sequence identity shared in their mature activeforms. 40 Thus, our assay for mouse and human serum GDF11 does not distinguish circulating GDF11 and GDF8. As a result, we did not accurately determine the changes of GDF11 in mice and in human.…”
Section: Discussionmentioning
confidence: 84%
“…18), and any of these could conceivably play a similar role to myostatin in muscle. Perhaps the most likely candidate is GDF-11͞BMP-11, which is highly related to myostatin in the mature region of the protein (2,23,24) and is also expressed in skeletal muscle. Genetic studies in mice have demonstrated clear roles for Gdf11 in regulating anterior͞posterior patterning (25), kidney development (25,26), neuronal development (27,28), and pancreas development (29).…”
Section: Resultsmentioning
confidence: 99%
“…Although such cleavage is sufficient for activating most TGFβ-like proteins (Hogan, 1996), prototypical family members TGFβ 1-3 remain noncovalently bound to their cleaved prodomains in latent complexes (Massague, 1998). More recently it has been demonstrated that GDF8 and 11, which share ~90% sequence identity in their mature regions (Gamer et al, 1999;Ge et al, 2005;Nakashima et al, 1999), are also noncovalently bound to their respective prodomains in latent complexes (Ge et al, 2005;Hill et al, 2002;Lee and McPherron, 2001;Wolfman et al, 2003) (Fig. 5B).…”
Section: Growth and Differentiation Factors 8 And 11 (Gdfs 8 And 11)mentioning
confidence: 99%